Effectiveness of Fertiliser Policy Reforms to Enhance Food Security in Kenya : A Macro-Microsimulation Analysis - Boulanger, Pierre; Dudu, Hasan; Ferrari, Emanuele; Mainar, Alfredo J.; Ramos, Maria Priscila (Taylor and Francis, 2022)
Food security represents a key challenge in most Sub-Saharan African countries and in Kenya in particular where still a relevant share of the population lives below a minimum dietary energy consumption. Kenya addresses this concern with a noteworthy policy mix, aiming at giving to the agricultural sector a leading task in improving food security. This paper evaluates the impacts on food security of expanding fertilizer capacities in Kenya, combined with a set of additional policy changes targeting fertilizer use. In a top-down analysis, a specific Computable General Equilibrium (CGE) model is linked with a microsimulation approach. Scenarios present overall positive effects on key food security aggregates. The same is true for welfare. Nevertheless, the heterogeneity of households across and within regions suggests that improving input productivity through better market access and service extension are critical to reducing possible discrepancies across farmers, households and regions. The paper concludes on the need for a sound policy mix since increasing fertilizer production alone is not enough to enhance food security evenly. Among accompanying measures, intensifying extension services are essential especially for smallholders in their acquisition of better knowledge on the use of agricultural inputs.